TRADISI TEI’ANO WINE PADA MASYARAKAT SIOMPU, SEBUAH RITUAL PRA TANAM (STUDI DI DESA NGGULA-NGGULA) - HAERUDDIN (Jurnal Pendidikan Sejarah, 2024)
This research aims; describes the background of the tei'ano wine ceremony in the Siompu community in South Buton Regency, describes the procession of carrying out the tei'ano wine ceremony in the Siompu community in South Buton Regency, reveals the symbolic meaning and values ​​contained in the tei'ano wine ceremony. The sources used consist of primary sources in the form of interviews, archives/documents, and secondary sources in the form of articles, books, magazines, journals, obtained from libraries and personal collections. This research uses a qualitative descriptive method. The aim of using this method is to create a systematic description, picture or painting of facts, characteristics and conclude data that has a relationship between the phenomena being studied. To obtain accurate data in connection with this research, in-depth interview techniques were used with the main informants and observation techniques or direct observations of the objects studied. Some of the main findings of this research are (1) The cultural tradition of tei'ano wine is a traditional ceremonial ritual of the farming community in Siompu. This ceremony is carried out after opening agricultural land, as an expression of prayer so that in the future the results will be abundant and free from pest pests. (2) The tei'ano wine ceremony or deliberation is carried out in baruga, which is attended by traditional institutions consisting of elements of sara and elements of law. (3) a. Social Values; deep wine tei'ano ritual Social life is essentially an activity of imitating and continuing the activities of humans in the past. b. Religious Values; The religious element in the tei'ano wine ceremony is reflected in the ritual of requesting the Almighty, so that the plants planted are kept away from pests and the results are bestowed. c. Cultural Values; The cultural value of the Tei'ano wine ceremony has become an ideology and justification for the importance of the ceremony. And if this culture is not implemented it will have a bad impact on people's lives